Posterior Cranial Fossa Meningiomas - Javalkar, Vijayakumar; Banerjee, Anirban Deep; Nanda, Anil (Journal of Neurological Surgery Part B: Skull Base, 2012)
This study evaluated the outcomes, complications, and recurrence rates of posterior cranial fossa meningiomas. We retrospectively reviewed our surgical experience with 64 posterior cranial fossa meningiomas. Mean age was 56 years with a female preponderance (67.2%). Headache was the most common symptom. Retrosigmoid approach was the commonest surgical procedure (23.4%). The incidence of cranial nerve related complications was 28%. Postoperatively facial nerve weakness was observed in 11%. The incidence of cerebrospinal fluid leak was 4.6%. Gross total resection was achieved in 37 patients (58%). Sixteen patients (25%) with residual tumors underwent Gamma knife radiosurgery. Recurrence or tumor progression was observed in 12 patients (18.7%). Operative mortality was 3.1%. At their last follow-up, 93% of the cases achieved Glasgow Outcome Scale scores 4 or 5. Total excision is the ideal goal which can be achieved with meningiomas located in certain location, such as lateral convexity, but for other posterior fossa meningiomas the close proximity of critical structures is a major obstacle in achieving this goal. In practicality, a balance between good functional outcome and extent of resection is important for posterior cranial fossa meningiomas in proximity to critical structures.
Keywords: posterior fossa; skull base; meningiomas